Dekonstruski Inferioritas Perempuan (Pendekatan Feminisme Agama) - Shulhan Al-finnas; Rusti Rahayu (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
This article is aimed to discuss about women position which is usually put in second part at social class. Deconstructing woman inferiority will be studied by using religious feminism at this article. This is result of qualitative research based on library study by looking at previous articles discuss the theme then analyzing them through religious feminism approach. The finding approves that emergence of sub-class woman are affected by people understanding about Islamic religious constructed by interpreter thoughts and Islam figures views which lead social believe and assumption. In addition, Â physical woman that needs man protection welcomes the emergence of women inferiority. Basically, the woman is created softly and weak more than man. It forces her to be protected by male like husband and enables him to arrogantly treat her inhuman.